miR-542 promotes mitochondrial dysfunction and SMAD activity and is raised in ICU Acquired Weakness - farre,garros; paul,R; connolly,M; lewis,A; natanek,SA; garfield,BE; BLoch,S; Mouly,V; griffiths,M; polkey,MI; Kemp,P (American Journal of Respiratory and Critical Care Medicine, 2017)
Rationale: Loss of skeletal muscle mass and function is a common consequence of critical illness and a range of chronic diseases but the mechanisms by which this occurs are unclear. Objectives: We aimed to identify miRNAs that were increased in the quadriceps of patients with muscle wasting and to determine the molecular pathways by which they contributed to muscle dysfunction. Methods: miR-542-3p/-5p were quantified in the quadriceps of patients with COPD and intensive care unit acquired weakness (ICUAW). The effect of miR-542-3p/5p was determined on mitochondrial function and TGF-β signaling in vitro and in vivo. Measurements and main results: miR-542-3p/5p were elevated in patients with COPD but more markedly in patients with ICUAW. In vitro, miR-542-3p suppressed the expression of the mitochondrial ribosomal protein MRPS10, and reduced 12S rRNA expression suggesting mitochondrial ribosomal stress. miR-542-5p increased nuclear phospho-SMAD2/3 and suppressed expression of SMAD7, SMURF1 and PPP2CA, proteins that inhibit or reduce SMAD2/3 phosphorylation suggesting that miR-542-5p increased TGF-β signaling. In mice, miR-542 over-expression caused muscle wasting, reduced mitochondrial function, 12S rRNA expression and SMAD7 expression, consistent with the effects of the miRNAs in vitro. Similarly, in patients with ICUAW, the expression of 12S rRNA and of the inhibitors of SMAD2/3 phosphorylation were reduced, indicative of mitochondrial ribosomal stress and increased TGF-β signaling. In patients undergoing aortic surgery, pre-operative levels of miR-542-3p/5p were positively correlated with muscle loss following surgery. Conclusion; Elevated miR-542-3p/5p may cause muscle atrophy in ICU patients through the promotion of mitochondrial dysfunction and activation of SMAD2/3 phosphorylation.